A study on the status of normoalbuminuric renal insufficiency among type 2 diabetes mellitus patients: A multicenter study based on a Chinese population. Issue 1 (30th October 2021) - Jia, Xiaomeng; Zang, Li; Pang, Ping; Jiang, Lina; Du, Jin; Gu, Weijun; Ba, Jianming; Mu, Yiming; Lyu, Zhaohui
Abstract: Background: Patients with normoalbuminuria and a reduced estimated glomerular filtration rate (eGFR) account for a considerable proportion of type 2 diabetes patients. The aim of this research was to investigate the epidemiological and clinical characteristics of normoalbuminuric kidney disease in a Chinese population. Methods: We included 8131 diabetic patients from a multicenter prospective study in China. Based on eGFR and urinary albumin‐to‐creatinine ratio (UACR), participants were stratified into four groups—normal albuminuria, albuminuria, normoalbuminuria with eGFR < 60 mL/min/1.73 m 2, and albuminuria with eGFR < 60 mL/min/1.73 m 2 . Clinical parameters and characteristics of patients with normoalbuminuria and eGFR < 60 mL/min/1.73 m 2 were retrospectively analyzed. Results: A total of 1060 out of 8131 individuals with diabetes had decreased eGFR (<60 mL/min/1.73 m 2 ). Normoalbuminuria accounted for 63.3% of participants with eGFR < 60 mL/min/1.73 m 2, and microalbuminuria and macroalbuminuria accounted for 30.1% and 6.3%, respectively. Patients with normoalbuminuria and reduced eGFR were more frequently male, older, and had higher levels of triglycerides than patients with normal albuminuria and eGFR. We also detected a correlation between lower extremity arterial disease, newly diagnosed diabetes, and normoalbuminuria‐reduced eGFR. Compared with participants with both albuminuria and eGFR decline, those with normoalbuminuria had better metabolic indicators, including systolic blood pressure and glycosylated hemoglobin, and shorter diabetes duration. Even in the normal range, UACR has a significant correlation with the risk of eGFR insufficiency. Conclusions: Normoalbuminuric renal insufficiency, characterized by male sex, older age, a higher level of triglyceride levels, and a higher risk of lower extremity arterial disease, accounted for a dominant proportion of diabetic patients with eGFR decline. Abstract : Highlights Approximately 63.6% of diabetes patients with an estimated glomerular filtration rate (eGFR) < 60 mL/min/1.73 m 2 have normal albuminuria. The factors related to normoalbuminuria and eGFR < 60 mL/min/1.73 m 2 were male sex, older age, higher triglyceride levels, lower extremity arterial disease, and a longer duration of diabetes. Compared with patients with both albuminuria and eGFR decline, those with normoalbuminuria have better control of metabolic indicators. 摘要: 背景: 蛋白尿正常和肾小球滤过率(eGFR)降低的患者在2型糖尿病(T2DM)患者中占相当大的比例。本研究旨在探讨中国人群正常蛋白尿肾病的流行病学及临床特点。 方法: 我们纳入了中国一项多中心前瞻性研究的8131例糖尿病患者。根据eGFR和尿白蛋白/肌酐比值(UACR)，参与者被分为四组:正常蛋白尿组、蛋白尿组、eGFR<60 mL/min/1.73 m 2 的正常蛋白尿组和eGFR<60 mL/min/1.73 m 2 蛋白尿组。回顾性分析正常蛋白尿、以及eGFR<60 mL/min/1.73 m 2 患者的临床数据及特点。 结果: 8131例糖尿病患者中有1060例eGFR降低(<60 mL/min/1.73 m 2 )。在eGFR<60 mL/min/1.73 m 2 的参与者中，正常蛋白尿占63.3%，微量蛋白尿占30.1%，大量蛋白尿占6.3%。与正常蛋白尿和eGFR患者相比，正常蛋白尿和eGFR降低的患者更多为男性，年龄更大，甘油三酯水平更高。我们还检测了下肢动脉疾病、新诊断糖尿病和正常蛋白尿eGFR降低之间的相关性。与同时有蛋白尿和eGFR下降的参与者相比，蛋白尿正常的参与者有更好的代谢指标，包括收缩压和糖化糖化血红蛋白，糖尿病时间更短。即使在正常范围内，UACR与eGFR功能不全风险显著相关。 结论: 正常蛋白尿的肾功能不全占糖尿病患者eGFR下降的主要比例，其主要特征包括:男性、年龄较大、三酰甘油水平较高和患下肢动脉疾病的风险较高。